The game variants in Europe. Trends and perspectives during youth competitive stages - Ângelo Miguel Pedregal Brito; José António Ribeiro Maia; Júlio Manuel Garganta; Ricardo Filipe Lima Duarte; Ana Maria Fite Alves Diniz (Universidade Estadual Paulista (UNESP), 2017)
Abstract AIMS The aim of this study was to verify how European countries manage the type of game variants and their frequency during different age groups of youth competition. METHODS Data were collected from the official rules of youth football championships. To identify countries homogenous groups according to their game variants, Two Step Cluster Analysis procedure was used while a nonparametric Kruskal-Wallis test was used to compare the game variants distribution in each Cluster. In order to correlate the game variants with age groups, a Chi-Square independence test and a Spearman ordinal correlation coefficient were used. RESULTS The results showed there were five clusters with significant differences in their game variants distribution (X2 kw (4) = 22.149; p<0.001; n = 30) and a significant correlation between age group and game variant (χ2(63) = 477.724; p<0.001; n = 30). Specifically, the most used game variants in each age group were the five-a-side (F5) in Under-8; the nine-a-side (F9) in Under-12; the seven-a-side (F7) in Under-9 and Under10; and the eleven-a-side (F11) in and above Under-13. CONCLUSION These results may contribute to understand the different country perspectives about the competitive game variants of youth football within the European space and its relation with diverse learning philosophies and pathways.